Special Issue Editorial on ‘Accounting for Anti-corruption in Social and Environmental Accounting Research’ - Apostol, Oana; Denedo, Mercy; Albu, Nadia; Albu, Catalin (Taylor & Francis, 2025)
The world is on the verge of collapsing on many fronts, facing interconnected crises such as climate warming, biodiversity loss and social inequality. We contend that corruption, alongside other systemic, institutional and individual factors, plays a significant role in aggravating these challenges. This special issue contributes to the lines of inquiry exploring the intricate interplay between corruption and social and environmental accounting (SEA). In this editorial, we begin by emphasising the significant role corruption plays in disrupting the advancement of the sustainability agenda and argue that it deserves a more prominent place in the SEA research. We propose three pillars for advancing the research agenda in this area and argue that SEA scholars are well-equipped to explore them in depth. We then reflect on the papers published in this special issue and their engagement with these themes.
Keywords: Corruption; social and environmental accounting(SEA); anti-corruption; governance; accountability; fi=Laskentatoimi|en=Accounting|